Biological information extracting device and biological information extracting system - NAKAMURA TSUYOSHI; TEZUKA TADANORI; OHASHI MASAHIRO; MATSUO MASATOSHI (2018)
This biological information extracting device includes: a camera that is provided at a head-mounted member mounted at the head of a person (subject) to capture temporally successive images including at least a part of the face of the person as a subject; a region selector that selects a skin color region from the images captured by the camera; a pulse wave detector that detects a pulse wave signalfrom the person on the basis of image data on the skin color region; and a data transmitter that transmits the pulse wave signal to a prescribed transmission destination, and the camera is directed to a side of the person's face and set to capture an image of a part of the side of the face (the cheek of the face). 生物体信息提取装置具备：照相机，其设置于头部穿戴体，拍摄在时间上连续的摄像图像，该头部穿戴体被穿戴于人物(被检体)的头部，该摄像图像包含人物的至少脸的部分作为被摄体；区域选择部，其从由照相机拍摄到的摄像图像中选择肤色区域；脉搏波检测部，其基于肤色区域的图像数据来检测人物的脉搏波信号；以及数据发送部，其将脉搏波信号发送到规定的发送目的地，照相机被配置为朝向人物的脸的侧面，从而设定为拍摄脸的侧面的部分(脸的脸颊)。